Lactococcus lactis strain FA1, FA2, FA3 and FA4 partial sequence of 16S ribosomal RNA gene isolated from Black tip shark (Carcahinus Limbatus) - Tengku Abdul Hamid, Tengku Haziyamin (2020)
This is a collection of partial sequence of 16S ribosomal RNA gene for Lactococcus lactis strain FA1, FA2, FA3 and FA4 isolated from Black tip shark (Carcahinus Limbatus). the sequences was submitted into NCBI genbank database and registered with accession numbers.